An Algorithm for Tuberculosis Screening and Diagnosis in People with HIV - Cain, Kevin P; McCarthy, Kimberly D; Heilig, Charles M; Monkongdee, Patama; Tasaneeyapan, Theerawit; Kanara, Nong; Kimerling, Michael E; Chheng, Phalkun; Thai, Sopheak; Thai, Le Hung; Sar, Borann; Phanuphak, Praphan; et al. (The New England journal of medicine, 2010)
Efficient, economical screening for active tuberculosis in resource-poor environments is a challenge. Screening is particularly important when there is coinfection with human immunodeficiency virus (HIV) and therefore concomitant consideration of initiation of antiretroviral therapy and the risk of the immune reconstitution syndrome. In this study of 1748 patients in Cambodia, Thailand, and Vietnam who were infected with HIV, an assessment for the presence of one of three symptoms — cough, fever, or night sweats — for more than 21 days over the preceding 4 weeks was found to have 93% sensitivity and 36% specificity for the detection of active tuberculosis infection. In this study of patients in Cambodia, Thailand, and Vietnam who were infected with HIV, an assessment for the presence of one of three symptoms — cough, fever, or night sweats — for more than 21 days over the preceding 4 weeks was found to have 93% sensitivity and 36% specificity for the detection of active tuberculosis infection. Tuberculosis is a leading cause of death among adults who are infected with the human immunodeficiency virus (HIV). 1 In some countries, death occurs in up to 50% of these patients during treatment for tuberculosis, usually within 2 months after tuberculosis has been diagnosed. 2 – 6 Delayed diagnosis of tuberculosis is probably an important contributor to high mortality. 7 Antiretroviral therapy can substantially reduce the risk of death, 2 , 4 but initiating this therapy in a patient with untreated tuberculosis can lead to the immune-reconstitution inflammatory syndrome. 8 – 13 To reduce the risk of tuberculosis, the World Health Organization (WHO) recommends the use of isoniazid . . .